Mixed-acid intercalation for synthesis of a high conductivity electrochemically exfoliated graphene. (January 2021) - Momodu, Damilola; Madito, Moshawe J.; Singh, Ashutosh; Sharif, Farbod; Karan, Kunal; Trifkovic, Milana; Bryant, Steven; Roberts, Edward P.L.
Abstract: Precise control of electrochemical intercalation and exfoliation conditions provides a method for tuning graphene properties. A systematic evaluation of the defects induced in graphene for varying intercalation times and intercalant composition is done using a sulphuric and phosphoric acid mixtures. Intercalation was performed in a concentrated mixture of sulphuric and phosphoric acid, followed by anodic exfoliation in aqueous ammonium sulphate solution. Multi-atom-doped graphene with primarily "boundary-type" defects is obtained, and the ratio of the defect-activated Raman modes showed a unique characteristics at 1600 s intercalation, irrespective of the intercalant composition. Careful selection of intercalation time is required to control the graphene defects. Phosphorus and nitrogen-doping increased with phosphoric acid content, influencing graphene properties. Interestingly, extending intercalation times beyond 1600 s deteriorated the electrical conductivity but enhanced the thermal stability with higher phosphoric acid content. We attribute this to loss of the sp 2 graphitic structure at higher intercalation times which dominates over contributions from the dopants. The highest electrical conductivity of ∼14, 000 S m −1 was two orders of magnitude higher than graphene obtained with pure sulphuric-acid intercalation. By adding phosphoric acid into the intercalant, the energy consumption and exfoliation time was reduced by 34% and by a factor of 3 respectively. Graphical abstract: Image 1